Use of historical documents in a digital world: comparisons with original materials and microfiche - Wendy M. Duff; Joan M. Cherry (Information Research: An International Electronic Journal, 2000)
The paper reports on a user study of a digital library collection of Early Canadiana material, with comparisons to the use of the material in original paper and microfiche formats. The study included a survey of individuals who had used Early Canadiana in original paper, microfiche or WWW format, focus group sessions, and server log analysis. The purpose of the study was to compare use and user satisfaction across the three formats to identify ways to improve the WWW format. Although, as expected, many people liked the paper format the best, over half of those who had experience with all three formats thought that the WWW format would be most useful in their work.  However, some users expressed concerns about the authenticity of the WWW format.  This raises questions for digital libraries to make explicit the relationship between the original paper and digital formats. The research led to 26 recommendations. To date, over half have been implemented or are in the process of being implemented.  The paper concludes with suggestions for future research.